School readiness screening and educational achievement at 9–10 years of age. (17th June 2021) - Shah, Rajesh; Brown, Gavin T L; Keegan, Peter; Harding, Jane E; McKinlay, Christopher J D; ,
Abstract : Aim: To determine whether a multi‐domain school readiness screening, the Before School Check (B4SC), identifies children at risk of low educational achievement and to compare the educational outcomes between those referred for intervention and those with B4SC concerns who were not referred. Methods: In this longitudinal cohort study of children born at risk of neonatal hypoglycaemia (N 331), the B4SC was performed at 4.5 years of age and a standardised curriculum‐based measure of educational achievement was completed at 9–10 years of age. Outcomes of school readiness screening were categorised into 'school readiness concern' or 'no school readiness concern' while 'below standard' and 'well below standard' ratings of educational achievement were combined into a single category of 'low educational achievement'. Results: Overall, 52% of children had ≥1 school readiness concerns at the B4SC, predominantly about behaviour (46%). Having ≥1 school readiness concern was associated with a nearly twofold increase in the likelihood of low academic achievement (OR 1.85, 95% CI 1.14, 3.02), which was apparent only for behaviour concerns. Of the 128 children with behaviour concerns, only 10 (8%) were referred for further interventions. There was a statistically non‐significant increase in the rates of low academic achievement among those referred than those non‐referred (60% vs. 47%). Conclusion: Identification of behaviour concerns during B4SC is associated with a moderate increase in the likelihood of low academic achievement at 9–10 years. Further, research is needed to determine how academic achievement can be improved in children with behaviour concerns at school entry.